Draft Genome Sequences of Novel Campylobacter Species Isolated from Nonhuman Primates - Mannion, Anthony (Microbiol Resour Announc, 2020)
Campylobacter species are being increasingly isolated and associated with disease in humans and animals. Here, we describe four draft genome sequences of Campylobacter species from nonhuman primates. These include Campylobacter troglodytis, isolated from wild chimpanzees, and two likely new Campylobacter species isolated from a lemur, common marmoset, and cotton-top tamarin.